Reframing the Business Case for Diversity: A Values and Virtues Perspective - Dijk, Hans van; Engen, Marloes van 1969-; Paauwe, Jaap 1953- (2012)
We provide an ethical evaluation of the debate on managing diversity within teams and organizations between equality and business case scholars. Our core assertion is that equality and business case perspectives on diversity from an ethical reading appear stuck as they are based on two different moral perspectives that are difficult to reconcile with each other. More specifically, we point out how the arguments of equality scholars correspond with moral reasoning grounded in deontology, whereas the foundations of the business case perspective are crafted by utilitarian arguments. We show that the problems associated with each diversity perspective correspond with the traditional concerns with the two moral perspectives. To resolve this stalemate position, we argue that the equality versus business case debate needs to be approached from a third, less well-known moral perspective (i.e. virtue ethics). We posit that a focus on virtues can enhance equality by reducing prejudice and illustrate this by applying it to the HRM domains of recruitment and selection and of performance management. Subsequently, we argue that values are key to aligning virtues with each other and with corporate strategy, delineate our values and virtues perspective on diversity, and argue why and how it can enhance organizational performance.
Keywords: Virtue Ethics; Utilitarianism; Deontology; HRM; Equality; (Managing) diversity